2013
DOI: 10.1371/journal.pone.0083020
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Cytological Changes in the Bone Marrow of Patients with Severe Fever with Thrombocytopenia Syndrome

Abstract: BackgroundPeripheral blood leucopenia and thrombocytopenia are the main manifestations in severe fever with thrombocytopenia syndrome (SFTS) patients. However, the underlying causes are poorly understood. Therefore, we aimed to investigate cytology of bone marrow samples collected from SFTS patients. Methods10 SFTS patients were identified by typical clinical manifestations, detection of peripheral blood leucopenia and thrombocytopenia, and nucleic acid-based detection of the newly identified bunyavirus. SFTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Serum levels of alanine aminotransferase, aspartate aminotransferase and lactate dehydrogenase are elevated [1,[39][40][41][42]. No cytological changes are seen in the bone marrow of SFTS patients, suggesting that the thrombocytopenia and leukopenia of SFTS do not result from damage to haematopoietic cells [43].…”
Section: Clinical Manifestations Pathology and Pathogenesismentioning
confidence: 94%
“…Serum levels of alanine aminotransferase, aspartate aminotransferase and lactate dehydrogenase are elevated [1,[39][40][41][42]. No cytological changes are seen in the bone marrow of SFTS patients, suggesting that the thrombocytopenia and leukopenia of SFTS do not result from damage to haematopoietic cells [43].…”
Section: Clinical Manifestations Pathology and Pathogenesismentioning
confidence: 94%
“…There is only one comparative study in the literature of bone marrow examination in SFTS patients and healthy volunteers, and no significant differences were found 15. In total, 10 SFTS patients underwent bone marrow aspiration, and the results were normal.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, reports regarding the bone marrow biopsy findings of SFTS patients are available. According to QuanTai et al, among 10 patients who underwent bone marrow biopsy, none exhibited hemophagocytosis in the bone marrow aspirate [7]. In contrast, Takahashi et al reported that among five SFTS patients who underwent bone marrow biopsy, all five exhibited hemophagocytosis in the bone marrow aspirate [2].…”
Section: Discussionmentioning
confidence: 99%
“…Upon examining the relevant clinical literature published, we found a few publications reporting patients with SFTS presenting with HLH [78]. So far, there has been no case report on SFTS associated with HLH in the English literature.…”
Section: Introductionmentioning
confidence: 99%